Pomegranate varieties different development stages transpiration of speed to himself special features (Texas Journal of Multidisciplinary Studies, 2023)
To increase the biomass of a plant organism by 1 g, approximately 500 g of water should be absorbed by the root system, assimilated by the plant and released into the atmosphere from the surface of its vegetative organs. Therefore, the study of the water regime is necessary for the formation of high crop productivity. To this end one of the main indicators of the water regime in different pomegranate varieties - the speed of transpiration in assimilative organs was studied.